Clinical and Methodological Considerations in Evaluating Amelogenesis Imperfecta as a Systemic Marker: A Critical Commentary - Edgar García-Torres; Oscar Eduardo Almeda-Ojeda; José Manuel Salas-Pacheco (Medical Science and Discovery, 2026)
Background and Objective: Recent literature frequently explores the clinical intersections between localized dental enamel variations and systemic health conditions. While multidisciplinary evaluations offer valuable clinical insights, premature conclusions regarding genetic etiologies can introduce significant clinical bias if acquired, pharmacological, and environmental confounders are overlooked. This commentary aims to critically examine a recent case report by highlighting key methodological and pathophysiological considerations. Main Topics Addressed: The analysis covers phenotypic classification under the Witkop framework, the physiological distinction between hereditary enamel patterns and acquired developmental defects, and the chronological limitations of utilizing adult presentations as markers of pediatric-onset processes. Furthermore, the discussion addresses unacknowledged metabolic and pharmacological confounders—such as proton pump inhibitor therapy and severe vitamin D deficiency—alongside the necessity of genetic validation and compliance with standardized reporting frameworks. Conclusions: Integrating these critical elements helps clinicians and researchers refine diagnostic precision, avoid premature clinical labeling, and enhance the overall quality and reliability of multidisciplinary medical documentation. Keywords: Amelogenesis Imperfecta; Renal Insufficiency, Chronic; Genetics; Vitamin D Deficiency; Case Reports.